Experimental validation of a HAM-BES co-simulation approach. (December 2017) - Ferroukhi, M-Y.; Belarbi, R.; Limam, K.; Bosschaerts, W.
Abstract: High levels of humidity in buildings lead to building pathologies. Moisture also has an impact on the indoor air quality and the hygrothermal comfort of the building's occupants. To better assess these pathologies, it is necessary to take into account the heat and moisture transfer between the building envelope and its indoor ambience. In this work, coupled heat, air and moisture transfer model in multilayer walls (HAM) was established. Thereafter, the HAM model is coupled dynamically to a building behavior code (BES). The coupling concerns a co-simulation between COMSOL Multiphysics and TRNSYS softwares. Afterward, the HAM-BES co-simulation accuracy was verified by conducting an experimental validation using an experimental device devoted to assess the hygrothermal response of building walls under several hygrothermal conditions. The comparison between numerical and experimental results showed good agreement with acceptable errors margins.